PERAN PEMERINTAH DESA DALAM MENANGANI PENYEBARAN COVID-19 PADA LANSIA (LANJUT USIA) DI DESA CEMARA JAYA KECAMATAN WASILE KABUPATEN HALMAHERA TIMUR - Wahyu Hidayati; Evelin J. R. Kawung; Cornelius Paat (HOLISTIK, Journal of Social and Culture, 2021)
Since the first case of Covid-19 was announced on March 2, 2020, the number of cases in Indonesia continues to increase and the Coronavirus or COVID-19 is very easy to spread. The elderly group is often associated with a group that is susceptible to various diseases because its physiological will gradually decrease including the body's immune system. The risk of complications from COVID-19 is higher. Cemara Jaya Village Government in handling the spread of COVID-19 in the elderly is to carry out social restrictions and lock down border areas and spray in every house and community environment. The Government of Cemara Jaya Village also provides education to the elderly regarding the dangers of COVID-19 in the elderly and applies the rules of wearing masks, sticking hands with soap, and keeping a distance.The Village Government also enforces a rule for violators of the rule, namely for all people who violate the rules of not wearing masks while traveling will be sanctioned in the form of self-isolation in their homes. During the COVID-19 pandemic, the Government of Cemara Jaya Village provided social assistance to the elderly in the form of rice, eggs, instant noodles, sugar and masks. The Village Government also provided cash assistance in the form of Rp 500,000, to eligible people such as the elderly, widowed mothers, and orphans during the COVID-19 pandemic.Keywords: elderly, pandemic, Covid-19